2011
DOI: 10.1007/s00401-011-0834-y
|View full text |Cite
|
Sign up to set email alerts
|

Vascular β-amyloid and early astrocyte alterations impair cerebrovascular function and cerebral metabolism in transgenic arcAβ mice

Abstract: Cerebrovascular lesions related to congophilic amyloid angiopathy (CAA) often accompany deposition of β-amyloid (Aβ) in Alzheimer’s disease (AD), leading to disturbed cerebral blood flow and cognitive dysfunction, posing the question how cerebrovascular pathology contributes to the pathology of AD. To address this question, we characterised the morphology, biochemistry and functionality of brain blood vessels in transgenic arctic β-amyloid (arcAβ) mice expressing human amyloid precursor protein (APP) with both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
195
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(211 citation statements)
references
References 64 publications
10
195
1
5
Order By: Relevance
“…The molecular mechanisms behind this are poorly understood, although human AD studies highlight that astrocyte/endothelial GLUT1 (as well as neuronal GLUT3) levels are reduced in post-mortem AD brains (99,100). Loss of astrocyte glucose transporters (GLUT1) is also found in the arcAβ (expressing both the Swedish and Arctic APP mutations) transgenic animal model, with no detectable changes in neuronal glucose transporters (97).…”
Section: Slc2a Glucose Transportersmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular mechanisms behind this are poorly understood, although human AD studies highlight that astrocyte/endothelial GLUT1 (as well as neuronal GLUT3) levels are reduced in post-mortem AD brains (99,100). Loss of astrocyte glucose transporters (GLUT1) is also found in the arcAβ (expressing both the Swedish and Arctic APP mutations) transgenic animal model, with no detectable changes in neuronal glucose transporters (97).…”
Section: Slc2a Glucose Transportersmentioning
confidence: 99%
“…Perturbed glucose metabolism is a contributing factor to the pathogenesis of AD (97,101,102). This disruption is reported to be one of the earliest features of AD, in that a reduction in brain glucose metabolism can be detected (103) and is used as a diagnostic tool (104).…”
Section: Relevance To Alzheimer's Diseasementioning
confidence: 99%
“…It has been shown that astrocyte changes precede widespread amyloid pathology and BBB disruption in a mouse model that develops plaques and CAA. 165 This suggests that Ab-induced astrocyte changes in AD may contribute to BBB dysfunction, but the mechanisms by which this occurs have yet to be determined.blood-brain barrier in Alzheimer's disease MA Erickson et al …”
mentioning
confidence: 99%
“…Aggregate forms of amyloid can modify glucose metabolism and oxidative stress in astrocytes, affecting neuronal cells and probably contributing to neuronal death (Allaman et al, 2010). Indeed, reduction of GLUT1 and MCT expression, as well as the retraction of of astrocyte endfeet occurs in Alzheimer's disease producing uncoupling of the neurovascular unit (Merlini et al, 2011). The activity of PPP is increased in Alzheimer's disease.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…Browen et al, Ferreira et al, 2010Harr et al, 1995;Hooijimans et al, 2007;Horwood & Davies, 1994;Kalaria & Harik,1989;;Langbaum et al, 2009;Liu et al, 2008;Merlini et al, 2011;Mooradian et al, 1997;;Nicholson et al, 2010;Ojaimi et al, 1999;Parker et al, 1994;Schapira et al, 2006;Shima et al, 2011;Simpson et al, 1994;Sims et al, 1983;Sorbi et al, 1983; Villain, 2010.…”
Section: Neuroscience -Dealing With Frontiersmentioning
confidence: 99%